(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Although the consideration of a popular and useful tool to support the creation of new enterprises and to develop existing businesses, the business model concept is used so widely and may have no clear meaning in practice. A thorough literature review showed that the concept is often discussed theoretically and conceptually, but there was a distinct lack of empirical studies of its conceptualization and application. This paper is intended to address this limitation in extant knowledge. The broad research in this paper also aimed to explore the conceptualization and application of the business model concept within SME business owner-managers. Subsidiary aims were to explore the concept’s perceived limitations and the ways that members of the own business managers have further refined the concept in order to address its shortcomings. To fulfill these aims, in-depth interviews were conducted with samples of 12 owner-managers of technology-based small businesses, all located in Nigeria. The research findings revealed a high level of diversity in the interpretation of the application in the business model concept and in evaluations of its use within and across the samples. And also, it’s offered a new application perspective. Only a few SME owner-managers applied the concept in any way, and some were unaware of the concept while others were afraid to apply the business model concept in their business.